Polimerisasi larutan akrilamid dengan mekanisme radikal bebas menggunakan metoda mixed-solvent precipitation - Boy Arief Fachri; R Rochmadi; Arief Budiman (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2004)
The most common method for producing polyacrylamide is solution polymerization. In this way, the polymer product is difficult to be separated. A method for overcoming this problem is using mixed solvent precipitation method. The kinetics aspect of free-radical polymerization of acrylamide using mixed-solvent precipitation method was studied. Acrylamide was polymerized in methanol-water solution with potassium persulfate as initiator. Two models of polymerization were proposed based on the initiation stage. Model I described the first order and the second order was represented by model 2. Polymerization of acrylamide was carried out in batch process. A methanol-water solution of acrylamide was charged into the flask and heated to the desired temperature. When the desired temperature was reached, the initiator potassium persulfate was introduced quickly into the reaction medium. Aliquots were taken from the reaction medium at a regular time then analyzed its polymer content by gravimetri method. Variables investigated were temperature (45-60°C), amounts of initiator (2.8.10-5-5.10-5 mole/mL) and monomer concentration (3.52.10-4-1.41.10-3 mole/mL). It can be concluded that both model 1 and model 2 can predict well the polymerization of acrylamide. The average error of model is less than model 2. Spesifically, the rate constant for every reaction in the models is got from the results of this experiment. Key Words : Acrylamide, Potassium Persulfate, Mixed-solvent Precipitation, Polymerization, The Kinetics Aspect Abstrak Polimerisasi larutan merupakan polimerisasi akrilamid yang paling umum, akan tetapi memiliki kelemahan dalam proses pemisahan polimer yang terbentuk. Polimerisasi akrilamid dengan mekanisme radikal bebas menggunakan metode mixed-solvent precipitation merupakan salah satu cara untuk mengatasi kelemahan tersebut. Penelitian ini dilakukan untuk mempelajari kinetika reaksi polimerisasi akrilamid melalui pengembangan model pada tahap inisiasi, yaitu model untuk order satu dan model 2 untuk order 2. Polimerisasi akrilamid dilakukan secara batch didalam labu leher tiga. Larutan akrilamid dimasukan ke dalam labu leher tiga dan dipanaskan mencapai suhu yang telah ditentukan, kemudian ditambahkan inisiator kalium persulfat (suhu dijaga tetap). Cuplikan diambil pada selang waktu tertentu dan kandungan polimer dianalisa dengan cara gravimetri. Peubah yang dipelajari meliputi variasi suhu (45-60 °C), jumlah inisiator (2.8.10 -5-5.5.10 -5 mol/mL) dan konsentrasi monomer (3.52.10-4-1.41.10-3 mol/mL). Berdasarkan hasil penelitian, dapat disimpulkan bahwa model 1 dan model 2 dapat menjelaskan kinetika polimerisasi akrilamid, akan tetapi model 1 memberikan ralat rata-rata yang lebih kecil dibandingkan dengan model 2. Secara spesijik, konstanta kecepatan untuk masing-masing reaksi dalam model diperoleh dari hasil percobaan ini. Kata Kunci : Akrilamid, Kalium Persulfat, Mixed-solvent Precipitation, Polimerisasi, Kinetika Reaksi